2023
DOI: 10.1186/s12882-023-03233-y
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a vegetarian diet on chronic kidney disease (CKD) progression – a systematic review

Abstract: Background A vegetarian diet is a popular alternative to the casual diet - it is considered healthy, and was proven to positively affect cardiovascular health. The Chronic Kidney Disease (CKD) progression is a major issue in the healthcare system, and constitutes a leading cause of death for 1.5% of the global population. The objective of this systematic review was to investigate the potential impact of a vegetarian diet on kidney function in CKD patients. Method … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
1
6
0
2
Order By: Relevance
“…Sin embargo, la preservación de la TFG se ha puesto en debate debido a que existe evidencia de que la DBP no solo ralentiza la disminución de la TFG, sino también mejora la función de filtración renal en pacientes con ERC (p= 0,001) (20) .…”
Section: Dietas Basadas En Plantas En El Manejo De La Ercunclassified
“…Sin embargo, la preservación de la TFG se ha puesto en debate debido a que existe evidencia de que la DBP no solo ralentiza la disminución de la TFG, sino también mejora la función de filtración renal en pacientes con ERC (p= 0,001) (20) .…”
Section: Dietas Basadas En Plantas En El Manejo De La Ercunclassified
“…Dysbiosis may result from factors like dietary habits, medications, physical activity, and underlying health conditions, further impacting kidney function and disease progression [64,65]. Nonetheless, both vegetarian and omnivore diets have their advantages and challenges when it comes to their impact on kidney affections, such as uremia and CKD [66]. A well-balanced vegetarian diet, rich in plant-based nutrients and carefully planned to ensure adequate protein intake, can be beneficial for managing CKD and reducing the risk of uremic toxin formation.…”
Section: Lifestyle Dietary Habits and Uremic Toxicitymentioning
confidence: 99%
“…These compounds intervene in the Maillard reaction mechanism (the reaction between reducing sugars and amino acids that occurs during food treatments at high temperatures). Uremic products obtained from this reaction are fructose-lysine, 3deoxyglucosone, glyoxal, methylglyoxal, pentosidine, Nε-carboxymethyl lysine, and Nε- Nonetheless, both vegetarian and omnivore diets have their advantages and challenges when it comes to their impact on kidney affections, such as uremia and CKD [66]. A wellbalanced vegetarian diet, rich in plant-based nutrients and carefully planned to ensure adequate protein intake, can be beneficial for managing CKD and reducing the risk of uremic toxin formation.…”
Section: Carbohydratesmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing clinical trial data have also shown that partial replacement of animal protein with plant protein leads to reductions in albuminuria [ 49 , 65 , 66 ]. Finally, a recent systematic review suggested that a vegetarian diet improves renal filtration function in CKD patients [ 67 ].…”
Section: Vegetarian Diets Incident Ckd and Ckd Progressionmentioning
confidence: 99%